Rose Macaulay and Propaganda. Issue 4 (September 2021) - Purdon, James
Abstract : The novelist Rose Macaulay (1881–1958) had direct professional experience of Britain's secret propaganda operation during the First World War. She was among the first British novelists to take propaganda seriously as a subject for fiction, and wrote insightfully about its methods and its social implications. Moreover, her long career illuminates both the continuity and the development of the British state's clandestine efforts to shape public opinion at home and abroad, from the beginnings of systematic, state-directed propaganda in the First World War to the more diffuse strategies of early Cold War anti-communism. Despite her close connections to propaganda in both world wars, however – and notwithstanding the interest her fiction very frequently takes in the worlds of official information, disinformation, and espionage – Macaulay has hardly figured in recent scholarship on the links between literature and national information systems. This article argues that Macaulay approached the challenge of reconciling propaganda and literature differently from many of her modernist contemporaries, refusing to abandon the idea of fiction as a persuasive and socially-engaged form of imaginative writing. If this position made her an outlier in the climate of reaction against propaganda which followed the First World War, it would, by the early years of the Cold War, seem much more tenable. In its first half, the article establishes Macaulay's bona fides as a participant in Britain's wartime propaganda establishment, and describes the impression this experience left on her early fiction. It then turns to Macaulay's final novel, The Towers of Trebizond, in which religious propaganda and anti-communist rhetoric combine, to great comic effect, in the febrile atmosphere of the Cold War middle east.